Agroecological reconversion of moorlands in Colombia: proposal for a farm’s classification tool - Rojas-Ramírez, Diego Alejandro (2024)
For the year 2018, law 1930 comes into force, which proposes the agroecological productive reconversion of agricultural activities in the moorlands of Colombia. This law requires the inclusion of people living and maintaining agricultural activities in the moorland in the reconversion processes but does not propose mechanisms to recognize the different forms of agriculture that exist in this ecosystem. Therefore, a tool was designed with the objective of classifying farms based on 9 criteria and 16 indicators. As part of its validation, the tool was compared with a commonly used statistical classification method. With the proposed method, four farm typologies were obtained where 6% of the sample was classified as near agroecological, 35% as traditional farmer, 10% as incipient agro-industrial and 48% as transitional producer. Statistically, no significant differences were found between the traditional farmer and the incipient agro-industrial farmer because they use similar agronomic management. The proposed tool prioritizes worldview and rootedness as much as productivity, unlike the statistical method that reduced the criteria for classification by prioritizing productive indicators. The proposed tool makes it possible to define particularized routes at the farm scale and to plan transition processes in compliance with the law, but incorporating real local capacities, available knowledge, and the family's cosmovision of the farm's future.